2018
DOI: 10.3233/jad-180065
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction as a Predictor and Driver of Alzheimer’s Disease-Like Pathology in OXYS Rats

Abstract: Growing evidence suggests that mitochondrial dysfunction is an early event in sporadic Alzheimer's disease (AD), but the impact of mitochondrial dysfunction on the transition from healthy aging to AD remains elusive. Here we estimated the influence of mitochondrial dysfunction on the initiation of AD signs in OXYS rats, which simulate key characteristics of sporadic AD. We assessed the mitochondrial ultrastructure of pyramidal neurons of the hippocampus at the age preceding the development (age 20 days), durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…This rat model simulates key characteristics of AD including tau protein hyper-phosphorylation, synaptic losses, neuronal cell death, behavioral alterations, and a decrease in cognitive functions on the background of increase in APP levels, enhanced accumulation of Aβ, and formation of amyloid plaques in the brain.The genome of OXYS rats lacking the mutations in the App, Psen1, and Psen2 genes, which are specific for the early form of AD, also speaks in favor of the this model matching the particular criteria of sporadic AD . According to our data, the development and progression of AD-like pathology in OXYS rats may be caused by mitochondrial dysfunction -2016, Kolosova et al, 2017, Tyumentsev et al, 2018). Here we summarize our evidence supporting the validity of this assertion.…”
supporting
confidence: 53%
“…This rat model simulates key characteristics of AD including tau protein hyper-phosphorylation, synaptic losses, neuronal cell death, behavioral alterations, and a decrease in cognitive functions on the background of increase in APP levels, enhanced accumulation of Aβ, and formation of amyloid plaques in the brain.The genome of OXYS rats lacking the mutations in the App, Psen1, and Psen2 genes, which are specific for the early form of AD, also speaks in favor of the this model matching the particular criteria of sporadic AD . According to our data, the development and progression of AD-like pathology in OXYS rats may be caused by mitochondrial dysfunction -2016, Kolosova et al, 2017, Tyumentsev et al, 2018). Here we summarize our evidence supporting the validity of this assertion.…”
supporting
confidence: 53%
“…One would expect that the effects of SkQ1 as an antioxidant are mediated by the suppression of ROS production. On the other hand, we have previously shown that the development of pathological signs in rats is accompanied by increasing mitochondrial dysfunction but not an increase in ROS production [29]. The therapeutic effects of supplementation with SkQ1 on the AD-like pathology in OXYS rats are associated with improvement of the mitochondrial apparatus and better neurotrophic supply [11,15].…”
Section: Oxys Oxys + Skq1mentioning
confidence: 90%
“…These alterations comprise mitochondrial gene expression changes, age‐dependent ultrastructural differences, and decreased activity of several ETC enzymes (Complexes I, IV, and V; Stefanova et al, ). A key pathogenic finding is that mitochondrial dysfunction precedes Aβ aggregation in the OXYS rat model (Stefanova et al, ; Tyumentsev et al, ). A more direct link between mitochondrial function and aging was demonstrated in a series of experiments, whereby dampening mitochondrial ROS production prolonged lifespan in mice (Schriner et al, ).…”
Section: Brain Metabolic/mitochondrial Dysfunction During Normal Agingmentioning
confidence: 99%